Methodological Pluralism in Economics: The ‘Why’ and ‘How’ of Causal Inferences - Maziarz, Mariusz (Filozofia Nauki, 2019)
Recently, two distinct notions of pluralism have been put forward in regard to research methods in economics: (1) model pluralism, stating that economists construct many theoretical models offering descriptions of actual or possible mechanisms and use different models for different purposes, and (2) evidential pluralism, according to which causal claims are established on the basis of theoretical conjecture and by observing the operation of a difference-making factor. In this paper, I make a case for methodological pluralism. I argue that economists not only use different research methods but also interpret their role in causal inference differently — depending on which (big-M) Methodological school they subscribe to. The argument proceeds by analyzing examples of recent economic research appealing to different Methodological commitments.